Net neutrality: Discrimination, competition, and innovation in the UK and US - Cooper, A; Brown, I (Association for Computing Machinery, 2015)
We analyze UK and US experiences as they relate to two central net neutrality questions: (1) whether competition serves as a deterrent to the discriminatory treatment of Internet traffic, and (2) whether discrimination creates barriers to application development and innovation. Relying on consumer switching behavior to provide more comprehensive competitive discipline was insufficient for a variety of reasons, including the presence of switching costs. The process of correcting errors in the technology used for application-specific management revealed that such management creates costs for application developers and innovators regardless of whether their products are targeted for traffic management or not.